Makna Tari Kejai Dalam Upacara Pesta Perkawinan Di Desa Topos Kecamatan Topos Kabupaten Lebong Provinsi Bengkulu - Suci Ramada Jayanti; Desfiarni Desfiarni; Nerosti Nerosti (SENDRATASIK UNP, 2019)
This article aims to describe and analyze the meaning of the Kejai Dance in a wedding Party in the Rejang society of Lebong Regency in Bengkulu Province. The type of this study was qualitative. The instruments used in collecting data were stationery, cameras, cellphone and handycam. The types of data in this study were primary and secondary data. The techniques of data collection were done by means of literature studies, observations and interviews. The steps in analyzing data were done by doing data reduction, data model (data display), withdrawal or verification conclusions. The results of the study indicate that the Rejang society of Lebong regency in Bengkulu Province has the Kejai Dance which has a social meaning matchmaking at a wedding party. The meaning is expressed in the movements of the Kejai dance as follows: (1) Sambah movement gives the sense of gratitude to Allah SWT so that it is given a smooth and straightforward work all that is to be done. (2) awal movement to begins the dance has the meaning that the society is always slow to do a job and always think first to make a decision. (3) Siap movement to get acquainted has good attitude and has good procedures. (4) Memberi dan menerima movement has the meaning that this society always receives whatever the results of the business they get in the form of gratitude. (5) Patah dayung movement has the meaning the society has a stand in every action and their hard work. (6) Sambah penutup movement has the meaning that every work that is done is always runs well and keeps returning to take care of it well whatever the results. Each movement has very deep meaning so that those show that the Kejai Dance includes life and social values in matchmaking betweenlackey and maid in the society of the Topos Village. The equipments (properties and costumes) give meaning to that society always has polite attitude and polite in dressing. The floor patterns mean that a married life is very simple but still solid and secure. The music instrument gives the meaning that the life of the Rejang area is also very simple. The Kejai Dance performance in a wedding party has an overall meaning which is the value of people's lives, responsibility and mutual respect as a binder of solidarity to strengthen the relationship among people.